2005
DOI: 10.1007/s10194-005-0205-y
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of allodynia, osmophobia and red ear syndrome in the juvenile headache: preliminary data

Abstract: The aim of the study was to determine the frequency of clinical allodynia, osmophobia and red ear syndrome in a young population. Medical records of the children admitted for headache between 1 December 2004 and 31 March 2005 were consecutively studied. A questionnaire was used to find the prevalence of allodynia, osmophobia and red ear syndrome. We visited 96 children with headache. The range of age was 6–18 years. We classified migraine in 57%, other primary headaches in 25% and secondary headaches in about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 16 publications
2
47
2
Order By: Relevance
“…The majority of studies investigated the presence of osmophobia. There were 13 comparative studies between migraine and other primary headaches or controls without headache, 2,3,5,8,13,14,[17][18][19][20]22,28,31 and 10 that evaluated only migraine patients. 4,6,7,11,15,16,24,26,29,30 As for odour-triggered headache, there were six studies detected, two comparative studies between migraine and other primary headaches, 1,3 two with migraine patients, 7,24 and two case reports.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of studies investigated the presence of osmophobia. There were 13 comparative studies between migraine and other primary headaches or controls without headache, 2,3,5,8,13,14,[17][18][19][20]22,28,31 and 10 that evaluated only migraine patients. 4,6,7,11,15,16,24,26,29,30 As for odour-triggered headache, there were six studies detected, two comparative studies between migraine and other primary headaches, 1,3 two with migraine patients, 7,24 and two case reports.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, we observed a severe intolerance to odours, pleasant or unpleasant, during headache attacks. 2,[4][5][6][7][8]10,11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] However, a limited number of studies showed that odours may trigger headache attacks in some patients, particularly in migraineurs 1,3,6,7,9,24 and occasionally in cluster headache patients. 12,18 This intolerance to odours is known as osmophobia, and according to two studies that investigated osmophobia in secondary headaches, it occurred during headache attacks only in the primary headaches.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is a significant association between odors and primary headaches, particularly to migraine with or without aura [1][2][3][4][5][6] and tension-type headache [1,[6][7][8]. The literature of its occurrence in secondary headaches is very scarce [9].…”
Section: Introductionmentioning
confidence: 99%
“…In migraine patients, prevalence of osmophobia during the headache attacks ranges from 20.0% to 81.7% [1,3,5,6,8,13] and in the period between headache attacks, this prevalence ranges from 24.0% to 53.3% [1,3,11,12]. Several categories of drugs are used in migraine prophylaxis, such as beta-adrenergic blockers, tricyclic antidepressants, calcium channel blockers, serotonergic antagonist, antiepileptics, and others [14][15][16].…”
Section: Introductionmentioning
confidence: 99%